On the Blue Comet - Wells, Rosemary (Candlewick Press, 2012)
When the Depression hits in Cairo, Illinois, and Oscar Ogilvie's father must sell their home and vast model train set-up to look for work in California, eleven-year-old Oscar is left with his dour aunt, where he befriends a mysterious drifter, witnesses a stunning bank robbery, and is suddenly catapulted onto a train that takes him to a different time and place.